Competition and Innovation: The Breakup of IG Farben - Felix Pöge (Institute of Labor Economics (IZA), 2022)
The relationship between competition and innovation is difficult to disentangle, as exogenous variation in market structure is rare. The 1952 breakup of Germany's leading chemical company, IG Farben, represents such a disruption. After the Second World War, the Allies occupying Germany imposed the breakup because of IG Farben's importance for the German war economy instead of standard antitrust concerns. In technology areas where the breakup reduced concentration, patenting increased strongly, driven by domestic firms unrelated to IG Farben. An analysis of patent texts shows that an increased propensity to patent does not drive the effect. Descriptively, IG Farben's successors increased their patenting activities as well, and their patenting specialized relative to the pre-breakup period. The results are consistent with a breakup-induced innovation increase by the IG Farben successors, which then spilled over to the wider chemical industry.
Keywords: O31; L44; N44; 330; innovation; competition; merger; antitrust; IG Farben